Modelling Deforestation Due to Human Population and Its Effect on Farm Fields (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, a nonlinear mathematical model is proposed and analyzed to study the deforestation due to human population and its effect on farm fields. We consider the variables namely, density of human population, density of trees and Farm fields. Both the growth rate and carrying capacity of trees, which follows logistic model, are assumed to be simultaneously depleted by density of human population. Further this affects the growth rate of crops in farm fields. We discretize the model by applying Foward Euler scheme and analyse the stability of the model. Finally, we provide some numerical simulations using MATLAB.
Keywords: Difference equations; Human population; Forest resources; Farm fields